Four-body decays of B meson with lepton number violation. (30th April 2018) - Yuan, Han; Wang, Tianhong; Jiang, Yue; Li, Qiang; Wang, Guo-Li
Abstract: The existence of heavy meson lepton number violating (LNV) processes shows the Majorana nature of the neutrino. Much of this theoretical and experimental researche focuses on this type of decay. Four-body epton-number violation (LNV) processes of the B meson may have sizable branching ratios as they share the same vertex and mixing parameters with the three-body case. Mixing parameters between the heavy Majorana neutrino and charged leptons extracted from the three-body case can be used to constrain the branching ratios of four-body decays of the B meson. So we can update the upper limits of these mixing parameters with new experimental data of the three-body LNV decays. We also analyze B 0 → D * − ℓ 1 + ℓ 2 + M 2 − using the updated parameters and estimate some channels' reconstruction events using current experimental data from Belle.